Immunity-Boosting Natural Herbs to Combat COVID-19 Pandemic: A Narrative Review - Saurabh Nimesh; Muhammad Akram; Md. Iftekhar Ahmad; Arshad Ahmad; Pratibha Kumari; Manohar Lal (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Coronaviruses cause some severe forms of respiratory infections such as Severe acute respiratory syndrome (SARS), Middle East respiratory syndrome (MERS), and Coronavirus disease 2019 (Covid-19). These viruses cause diarrhea in pigs and cows and upper respiratory disease in chickens, while other symptoms may differ. In humans, a total of six coronaviruses have been identified HCoVs-NL63, HCoVs-OC43, HCoVs-229E, HCoVs-HKU1, MERS-CoV, and SARS-CoV. The world health organization (WHO) has done a great deal of hard work regarding combating the monstrous effects of this virus. So far, no specific antiviral drugs have been developed for the treatment of Covid-19. Therefore, the medicinal plants used for the previous epidemic outbreaks are getting attention for their potential treatment against the virus. It has been reported that 70 to 80% of people in developing countries depend on medicinal plants or phytomedicine compared to allopathic drugs for their primary healthcare. The south Asian subcontinents have used almost up to 25,000 formulations and extracts obtained from medicinal plants for treatment in folk medicine. The present review discusses an overview of the coronavirus, its immune responses, and some immunity-boosting herbs to combat Covid-19.